How to catch a black swan: Measuring the benefits of the premortem technique for risk identification. Issue 2 (2nd April 2016) - Gallop, David; Willy, Chris; Bischoff, John
ABSTRACT: Projects face the challenge of increasing complexity and uncertainty leading to more black swans (hard-to-predict, potentially catastrophic risks) in our future. Within the two schools of risk ( objective and subjective ), we theorize the latter is the key to early identification of the black swan. Creativity-based risk identification techniques are not bound by the historical data and precedence but teams must overcome deliberate ignorance for meaningful collaboration. This study compares two creativity-based risk identification techniques—brainstorming and premortem. The premortem is the theoretical opposite of a postmortem. In a postmortem, the investigator determines the cause of death after the patient has died. The premortem calls for a team to imagine the project has failed and deduce causes for the failure. The team then proposes changes to the project plan to address causes of the failure. We conclude that teams using the premortem technique identified better quality risks, more quality changes to the plan, and identified more black swan risks than their brainstorming counterparts.